(untitled) (Semiárida, 2020)
This work has been done in the Ranch La Baya Vieja. Dpto. Toay, province of La Pampa, to determine the dry weight of deep roots (0-20 and 20-40 cm) and crowns of a grassland of Poa ligularis and Piptochaetium napostaense in winter time, and Bothriochloa springfieldii and Rhynchosia senna in summer time. Along a year and every thirty days we took samples to determine the dry weight of roots and crowns. The total average weight of the roots (0-20 cm) was 1869.8 gMS/m2. The roots (20-40 cm) showed an annual total average weight of 623.2 gMS/m2. At a depth of 20 cm we found 75% of the root volume. The remaining 25% was found at a depth between 20-40 cm. The crowns reached an average weight of 218.7 gMS/m2.